Gene Expression Comparison Between Primary Triple Negative Breast Cancer and Paired Axillary and Sentinel Lymph Node Metastasis - Srour, Marissa K. (Breast J, 2019)
PURPOSE: Few studies examine the genomics of axillary lymph node (ALN) metastasis in triple negative breast cancer (TNBC). The aim was to characterize and compare gene expression patterns of primary breast cancers and paired ALN metastases. METHODS: Patients with stage 2–3 ER/PR negative, HER2 negative TNBC with ALN macrometastasis without neoadjuvant therapy were selected. Tumor-specific area was isolated from breast and ALN tissue sections. Gene expression of 2,567 cancer-associated genes was analyzed with the HTG EdgeSeq system coupled with Illumina Next Generation Sequencing (NGS). RESULTS: 17 pairs of TNBC and autologous ALN metastasis were analyzed. Compared with the primary, ALN metastasis had 257 statistically significant differentially expressed genes, including 123 upregulated genes and 134 downregulated genes. Notably, there was an upregulation of anti-apoptosis and survival signaling genes (BIRC3, TCL1A, FLT3, VCAM1) in the ALN metastasis. There was also an upregulation of chemotaxis genes (CCL19, CCL21, CXCL13, TNFSF11). The most striking feature is the downregulation of genes known to regulate cell microenvironment interaction (MMP2, MMP 3, MMP 7, MMP 11, MMP14, COL1A1, COL1A2, COL3A1, COL5A1, COL5A2, COL6A6, COL11A1, COL17A1). CONCLUSION: In TNBC, ALN metastases have a distinct gene expression profile. Genes associated with anti-apoptosis, survival responses, and chemotaxis are upregulated, and genes associated with regulation of extracellular matrix are downregulated when compared to autologous primary cancer. TNBC cells metastatic to lymph nodes undergo a change in order to metastasize and survive in the new microenvironment, which may lead to insights into the metastatic process